A semi-strong perfect digraph theorem. Issue 3 (1st September 2020) - Andres, Stephan Dominique; Bergold, Helena; Hochstättler, Winfried; Wiehe, Johanna
Abstract: Reed (1987) showed that, if two graphs are P 4 -isomorphic, then either both are perfect or none of them is. In this note, we will derive an analogous result for perfect digraphs.